The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1806-9282.64.01.22
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of curcumin nanoparticles protects ischemia-reperfusion injury in ovaries: An animal model study

Abstract: Intraperitoneal administration of nanocurcumin can be helpful in minimizing ischemia-reperfusion injury in ovarian tissue exposed to ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…After this stage, the Bcl-2 prohibits the apoptosis that triggers the cellular proliferation. 18 Our RT-PCR analyses showed that in MRSA/CNP/ HAMLET group, caspase 3, Bcl-2, and p43 expressions were increased. Thus, it could be concluded that curcumin nanoparticles in presence of HAMLET could enhance the cellular proliferation by upregulating the caspase 3, Bcl-2, and p43 expressions.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…After this stage, the Bcl-2 prohibits the apoptosis that triggers the cellular proliferation. 18 Our RT-PCR analyses showed that in MRSA/CNP/ HAMLET group, caspase 3, Bcl-2, and p43 expressions were increased. Thus, it could be concluded that curcumin nanoparticles in presence of HAMLET could enhance the cellular proliferation by upregulating the caspase 3, Bcl-2, and p43 expressions.…”
Section: Discussionmentioning
confidence: 66%
“…Antioxidant activities including superoxide dismutase (SOD), total nitric oxide synthase (tNOS), malondialdehyde (MDA), myeloperoxidase (MPO), total glutathione (tGSH), glutathione peroxidase (GPO), glutathione reductase (GSHRd), glutathione S-transferase (GST) analyses, isolation of DNA from tissue, and cDNA hydrolysis with formic acid measurement of 8-hydroxy-2′deoxyguanosine (8-OH Gua) were performed based on methods described by others. 18 Histological Preparation and Quantitative Morphometric Studies. The tissue samples were taken on 7, 14, and 21 days after surgery from periphery of the wound along with normal skin and fixed in 10% buffered formalin, dehydrated and embedded in paraffin wax, sectioned at 5 µm, and stained with hematoxylin and eosin (H&E) and Masson's trichrome stains.…”
Section: Biochemical Studiesmentioning
confidence: 99%
“…100 mg/kg curcumin 2. 1 mg/kg nano curcumin Intraperitoneal Group SSG: laparotomy only Group I: 3 h ischemia only Group I/R: 3 h ischemia and 3 h reperfusion Group I/C: 3 h ischemia only and 100 mg/kg curcumin Group I/R/C: 3 h ischemia, 3 h reperfusion and 100 mg/kg curcumin Group I/NC: 3 h ischemia only and 1 mg/kg nano curcumin Group I/R/NC: 3 h ischemia, 3 h reperfusion and 1 mg/kg nano curcumin -Nanocurcumin-treated animals showed significantly improved development of ischemia and reperfusion tissue injury compared with other groups -I/R/NC group showed significantly higher superoxide dismutase values, total glutathione, glutathione peroxidase, glutathione reductase and glutathione S-transferase than other groups (p < 0.05) -I/R/NC group showed a significantly lower value of nitric oxide synthase, malondialdehyde, myeloperoxidase and 8-hydroxy-2 deoxyguanine levels compared with other Groups -No difference in all biochemical parameters in other groups [69] CBA female mice immunised with an extract from the ovaries of outbred albino mice to induce immune disease of the ovaries (model of autoimmune disease in women) Curcumin at 100 µg/g (four times a week) Intragastric -The percentage of oocytes in metaphases I and II: Immunised mice: the numbers of oocytes with dissolved germinal vesicle (metaphase I) and the formed polar body (metaphase II) decreased significantly Curcumin-treated mice: the level of oocytes in metaphases I and II increased significantly compared with the immunised group -The number of apoptotic and necrotic cells in the thymus, spleen and lymph node:…”
Section: Effect Of Curcumin On Ovarian Diseasesmentioning
confidence: 79%
“…Interestingly, in another rat model of ovarian ischemia–reperfusion injury, 1 mg/kg nano curcumin improved the oxidative status parameters but not 100 mg/kg. These results included significantly higher values of superoxide dismutase, total glutathione, GSH, glutathione reductase and glutathione S-transferase and substantially lower values of nitric oxide synthase, MDA, myeloperoxidase and 8-hydroxy-2 deoxyguanine levels [ 69 ]. The findings from these two studies showed that nanocurcumin at very low concentrations (1 mg/kg) produced significant improvements compared to the native curcumin (100 mg/kg and 200 mg/kg curcumin), which might be attributed to its high bioavailability and longer half-life.…”
Section: Effect Of Curcumin On Ovarian Diseasesmentioning
confidence: 99%
“…In damaged tissue, increase in the levels of p53 and caspase is observed to trigger apoptotic activity of the immune cells that results in the exclusion of the immune cells. Following this phase, the Bcl-2 inhibits the apoptotic activity that induces the proliferation of cells [ 34 ]. In the present study, analyses of RT-PCR indicated that in INFCTD-HMLT-CNM animals, expressions of caspase 3, Bcl-2, and p43 were amplified.…”
Section: Discussionmentioning
confidence: 99%